Pembuatan Mobile E-Learning Berbasis Android - Liliana, Liliana; Soesanto, Daniel; Rahardjo, Kevin Sebastian (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2024)
Abstract—E-Learning utilizes information and communication technology for learning. Most universities use e-learning-based websites. However, currently website-based e-learning is not enough because of technological developments which have resulted in more and more smartphone users and require Android-based mobile applications to improve learning. In this study, distributing questionnaires and making observations on similar systems. Based on the results of the questionnaire, the problems faced are that students do not know or forget if there is an assignment and there is no communication feature that can be used in e-learning. From these problems, an e-learning mobile application was created so that lecture materials and assignments can be accessed via smartphones and help communication. The application is developed with Angular Ionic framework with MySQL DBMS. The main features created are creating resources, creating reminders and notifications, sending assignments and quizzes, and private chat and group chat features. Based on the results of trials and evaluations, it was found that the end of the application was that it could assist lecturers in delivering material, perform assignments or quizzes and assist students in accessing material and doing quizzes via smartphones. In addition, the application made also helps students communicate with lecturers through chat. Keywords: android, e-learning, mobile Abstrak—E-Learning memanfaatkan teknologi informasi dan komunikasi untuk pembelajaran. Pada universitas umumnya menggunakan e-learning berbasis website. Namun, saat ini e-learning berbasis website belum cukup karena perkembangan teknologi mengakibatkan pengguna smartphone semakin banyak dan membutuhkan aplikasi mobile berbasis android untuk meningkatkan pembelajaran. Pada penelitian ini, disebarkan kuesioner dan dilakukan pengamatan pada sistem sejenis. Berdasarkan hasil kuesioner, masalah yang dihadapi yaitu mahasiswa tidak tahu atau lupa jika ada tugas serta belum adanya fitur komunikasi yang dapat digunakan pada e-learning Dari permasalahan tersebut, dibuat aplikasi mobile e-learning sehingga materi dan tugas perkuliahan dapat diakses melalui smartphone serta membantu komunikasi mahasiswa dengan dosen. Aplikasi dikembangkan dengan Bahasa pemrograman typescript dengan framework ionic angular dengan DBMS MySQL. Fitur utama yang dibuat adalah membuat resource perkuliahan, membuat pengingat dan notifikasi, mengirim dan menerima tugas serta quiz, dan fitur private chat dan group chat. Berdasarkan hasil uji coba serta evaluasi, didapatkan kesimpulan bahwa aplikasi yang dibuat dapat membantu dosen dalam menyampaikan materi, tugas, quiz serta melakukan penilaian tugas ataupun quiz dan membantu mahasiswa dalam mengakses materi serta mengerjakan tugas serta quiz melalui smartphone. Selain itu, aplikasi yang dibuat juga membantu komunikasi mahasiswa dengan dosen melalui chat. Kata kunci: android, e-learning, mobile